2011
DOI: 10.1152/ajpregu.00840.2010
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-methylbutyrate reduces myonuclear apoptosis during recovery from hind limb suspension-induced muscle fiber atrophy in aged rats

Abstract: β-Hydroxy-β-methylbutyrate (HMB) is a leucine metabolite shown to reduce protein catabolism in disease states and promote skeletal muscle hypertrophy in response to loading exercise. In this study, we evaluated the efficacy of HMB to reduce muscle wasting and promote muscle recovery following disuse in aged animals. Fisher 344×Brown Norway rats, 34 mo of age, were randomly assigned to receive either Ca-HMB (340 mg/kg body wt) or the water vehicle by gavage (n = 32/group). The animals received either 14 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 92 publications
13
116
3
2
Order By: Relevance
“…Animal studies have shown that supplemental HMB may enhance protein synthesis in neonatal skeletal muscle by stimulating translation initiation (Wheatley et al, 2014), which may improve survival rates of low-birth-weight infants. In addition, HMB supplementation suppresses apoptotic signaling and the apoptotic index during muscle disuse and during reloading periods after disuse in aged rats (Hao et al, 2011) and improves proliferation of satellite cells in muscles from aged rats in response to a loading stimulus following a period of disuse (Alway, Pereira, Edens, Hao, & Bennett, 2013). Population surveys suggest that HMB can be used to enhance recovery by attenuating exercise induced skeletal muscle damage in trained (Wilson et al, 2013b) and untrained populations (Wilson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that supplemental HMB may enhance protein synthesis in neonatal skeletal muscle by stimulating translation initiation (Wheatley et al, 2014), which may improve survival rates of low-birth-weight infants. In addition, HMB supplementation suppresses apoptotic signaling and the apoptotic index during muscle disuse and during reloading periods after disuse in aged rats (Hao et al, 2011) and improves proliferation of satellite cells in muscles from aged rats in response to a loading stimulus following a period of disuse (Alway, Pereira, Edens, Hao, & Bennett, 2013). Population surveys suggest that HMB can be used to enhance recovery by attenuating exercise induced skeletal muscle damage in trained (Wilson et al, 2013b) and untrained populations (Wilson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis for the delayed recovery of muscle mass with remobilization is unknown. One potential mechanism could be linked to myonuclear apoptosis that occurs during immobilization and is still prevalent during reloading (27,51). It is also tempting to speculate that it may be related to a reduction in RNA content, and thus ribosome abundance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HMB could improve muscle recovery in old rats with sarcopenia that had been subjected to unloading, in part via an increase in satellite cell proliferation and a reduction of nuclear apoptosis (Hao et al, 2011). HMB also has been shown to have direct effects on proliferation of myoblasts in vitro (Kornasio et al, 2009), although, its efficacy on satellite cell activation has not previously been evaluated in vivo in aged immobilized animals.…”
Section: Modulation Of Satellite Cell Function In Sarcopenia Via Nutrmentioning
confidence: 99%